2005
DOI: 10.1055/s-2005-873056
|View full text |Cite
|
Sign up to set email alerts
|

Oculomotor Nerve Schwannoma Mimicking Ophthalmoplegic Migraine

Abstract: Ophthalmoplegic migraine (OM) is a rare variant of migraine characterized by recurrent attacks of severe headache followed by oculomotor nerve palsy. The recent revision of the International Headache Classification has reclassified OM from a subtype of migraine, defined as a functional headache, to the neuralgia category. We describe a case of an 11-year-old girl with pathologically confirmed oculomotor nerve schwannoma who had been suffering from symptoms mimicking OM. For five years, she has been under treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 8 publications
1
30
0
2
Order By: Relevance
“…5 To the best of our knowledge, to date only 38 cases of oculomotor nerve schwannomas have been reported in the literature, including 15 male and 23 female patients with an age range from 8 to 74 years. 3,[5][6][7][8][9][10][11][12][13][14] Preoperative oculomotor dysfunction was manifested in 30 cases out of 38, and also in our patient. The tumor was located in the orbit in just…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…5 To the best of our knowledge, to date only 38 cases of oculomotor nerve schwannomas have been reported in the literature, including 15 male and 23 female patients with an age range from 8 to 74 years. 3,[5][6][7][8][9][10][11][12][13][14] Preoperative oculomotor dysfunction was manifested in 30 cases out of 38, and also in our patient. The tumor was located in the orbit in just…”
Section: Discussionsupporting
confidence: 62%
“…four cases (solitary orbital type), in the subarachnoid space in 17 cases (cisternal type), in the cavernous sinus in 12 cases (cavernous type), extending from the cavernous sinus to the cistern in five cases (cisterno-cavernous type) and extending from cavernous sinus to the orbit in one case. 3,[5][6][7][8][9][10][11][12][13][14] Our case is unusual due to a number of reasons. The age of our patient is of interest as most of these cases have been reported in middle aged patients with the youngest reported patient being only eight years old.…”
Section: A B C Bmentioning
confidence: 87%
“…7 Katoh et al and Murakami et al reported that oculomotor nerve schwannomas were preoperatively misdiagnosed as meningiomas or trigeminal schwannomas (in a cistocavernous location of the oculomotor schwannoma). 7,15 Kachhara et al have described one case of a patient suffering from a cistocavernous oculomotor schwannoma and surgery performed under the preoperative suspicion of a suprasellar meningioma. 6 Therapeutical strategies include a wait-and-see policy (preferred by Katoh et al 7 ), gamma knife surgery, and resection.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, oculomotor nerve schwannomas present with various degrees of oculomotor nerve palsy, ptosis, diplopia, pain in the distribution of the first branch of the trigeminal nerve 3,4,9,12,13,15,16,18 and may be associated with neurofibromatosis type 2. In the literature, we found 3 case reports of an oculomotor nerve schwannoma mimicking ophthalmoplegic migraine in younger patients, 1,8,15 and 3 other case reports of an asymptomtic schwannoma of the oculomotor nerve. 2,7,10 Schwannomas originating from the oculomotor nerve are extremely rare.…”
Section: Introductionmentioning
confidence: 99%
“…Because numerous diseases can mimic OM, such as vascular aneurysm, myasthenia gravis, oculomotor nerve schwannoma, pituitary apoplexy, Tolosa-Hunt syndrome, mucomycosis and ischaemic or idiopathic cranial palsy, paraclinical examinations are always required [4,5]. In published cases as in ours, biological blood tests are sometimes carried out to rule out diabetes mellitus, myasthenia gravis or an inflammatory disease [3,4,11]. To date, there is no consensus on the tests and ICHD II does not recommend making such biological investigations and gives no guidelines for blood tests.…”
Section: Discussionmentioning
confidence: 99%